Microstructure and Mechanical Properties of BCC-FCC Eutectics in Ternary, Quaternary and Quinary Alloys From the Al-Co-Cr-Fe-Ni System - Röhrens, Daniel; Navaeilavasani, Niloofar; Stryzhyboroda, Oleg; Swientek, Fabian; Pavlov, Paul; Meister, Dirk; Genau, Amber; Hecht, Ulrike (Frontiers in Materials, 2020)
This study aimed at understanding the structure and properties of dual-phase eutectics in ternary, quaternary and quinary alloys of the Al-Co-Cr-Fe-Ni system. The alloys at case were (i) Ni48Fe34Al18, (ii) Ni44Fe20Cr20Al16 and (iii) Ni34.4Fe16.4Co16.4Cr16.4Al16.4. Samples in form of cylindrical bars, dia. 10 mm x 150 mm, were produced by arc melting and suction casting from pure elements (> 99.9 wt%). Bridgman solidification at low growth velocity was used to produce additional samples with large eutectic spacing and lamellae thickness of the two phases BCC-B2 and FCC in order to facilitate phase characterization by energy dispersive x-ray analysis (SEM / EDS) and nano-indentation. In agreement with thermodynamic calculations, each of the phases was found to be multi-component and contain all alloying elements in distinct amounts. The mechanical properties of the individual phases were analyzed in relation to their composition using nano-indentation experiments. These measurements revealed some insights into “high-entropy effects” and their contribution to the elastoplastic response to indentation loading. Further analysis focused on as-cast as well as heat-treated samples comprising phase fraction measurements, micro-indentation and miniature testing in three point bending configuration. For optimum heat treatment conditions, a good balance of strength and ductility was obtained for each of the investigated alloys. Further work is necessary in order to assess their capability as structural materials.